FACTORS AFFECTING THE LEVEL OF BANK HEALTH CASE STUDY AT PT BANK MANDIRI (PERSERO) TBK (British Journal of Global Ecology and Sustainable Development, 2023)
This research aims to evaluate the level of bank health at PT Bank Mandiri (Persero) Tbk. The data used is quantitative data in the form of financial reports. The analysis technique used is descriptive analysis, namely by using Capital, Asset, Management, Earning and Liquidity factors. The research results show that Bank Mandiri's health level is in a healthy condition, meaning that the bank is able to carry out normal banking operational activities and is able to fulfill all its obligations properly in ways that comply with applicable banking regulations with a score of 93.07 in 2018. 87.17 in year 2019 and 89.46 in 2020.